Implementasi Problem Based Learning di Sekolah Dasar: Sebagai Upaya Meningkatkan Hasil Belajar - Rulef, Anggur Reksa Putri; Andika, Refiona; Ariani, Yetti; Nisa, Sahrun (Lembaga Yasin AlSys, 2025)
This research is motivated by the low level of learning outcomes among fifth-grade elementary school students in mathematics. The purpose of this study is to examine and analyze the implementation of the Problem-Based Learning model in improving students' learning outcomes in mathematics. This research is a Classroom Action Research (CAR) using both qualitative and quantitative approaches, consisting of two cycles: Cycle I with two meetings and Cycle II with one meeting. The analysis results show that after conducting the research in Cycle II, the knowledge scores increased to 90%, categorized as good. Therefore, it can be concluded that the Problem-Based Learning model is effective in improving mathematics learning outcomes for fifth-grade elementary school students. Based on the research results showing a significant improvement in students’ mathematics learning outcomes through the implementation of the Problem-Based Learning model, it is recommended that teachers and school authorities systematically integrate the Problem-Based Learning model into the mathematics learning process in fifth-grade classes.